The abundance of anoa (Bubalus sp.) Plant at Bogani Nani Wartabone National Park - Diah Irawati Dwi Arini; Nurlita Indah Wahyuni (Jurnal Penelitian Kehutanan Wallacea, 2016)
Bogani Nani Wartabone National Park (TNBNW) is an important habitat for anoas, which represents genetic diversity of anoa species in the northern area of Sulawesi. Wild animals depend on their habitats for many things, including food. Food availability influences the growth and reproduction of any species. Food information is also important for area management as an input in habitat development activities, which are parts of in-situ conservation. The aim of this study was to investigate the types, abundance and diversity of anoa food plants in TNBNW. The study was conducted in three locations, namely Imandi Mountain, Gambuta Mountain and Sinombayuga Mountain ranging between 0 and 1600 mdpl elevations. Data were collected using line plot sampling method and food type observation was performed with plots size of 0.04 ha. Total observation plots in three research locations were 202, of which 90 plots were in Imandi Mountain and Gambuta Mountain, and 22 plots were in Sinombayuga Mountain. Data were analyzed descriptively and presented in tables. Food abundance was determined by total food plants found in every location. Natural plants food diversity used several indices, which were Margalef Richness, Shannon-Wiener Diversity Index and Evenness Index. The results showed that 35 species of food plants were identified. As many as 28 species of them including herbaceous plants, and seven species of woody plants. Some plant species have higher abundance, namely rofu (Elatostema sp.), rattan (Calamus sp.), and various types of fern.